2017
DOI: 10.1111/mec.14044
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the sergeantsAbudefduf sexfasciatusandA. vaigiensisreveals complex introgression patterns between two widespread and sympatric Indo‐West Pacific reef fishes

Abstract: On evolutionary timescales, sea level oscillations lead to recurrent spatio-temporal variation in species distribution and population connectivity. In this situation, applying classical concepts of biogeography is challenging yet necessary to understand the mechanisms underlying biodiversity in highly diverse marine ecosystems such as coral reefs. We aimed at studying the outcomes of such complex biogeographic dynamics on reproductive isolation by sampling populations across a wide spatial range of a species-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 88 publications
6
26
0
Order By: Relevance
“…Molecular results obtained here are in agreement with data reported by Bertrand et al [27], who noticed that an A. vaigiensis lineage was found to be nested within A. sexfasciatus in the mitochondrial gene tree, whereas both species were only found to be distinct based on nuclear information. Alternatively, another possibility is that some misidentifications may be at the basis of the sequences deposited in GenBank.…”
Section: Discussionsupporting
confidence: 93%
“…Molecular results obtained here are in agreement with data reported by Bertrand et al [27], who noticed that an A. vaigiensis lineage was found to be nested within A. sexfasciatus in the mitochondrial gene tree, whereas both species were only found to be distinct based on nuclear information. Alternatively, another possibility is that some misidentifications may be at the basis of the sequences deposited in GenBank.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, genetic variation of mitochondrial and two nuclear loci was examined across much of the geographic range of A. sexfasciatus and A. vaigiensis by Bertrand, Borsa & Chen (2017) . That study identified four highly distinct A. vaigiensis lineages , which did not form a monophyletic group relative to other closely related species those authors examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although the genus has been subject to much recent phylogenetic study, those analyses used few genetic loci and did not include all known species within the genus. As a consequence, uncertainty persists regarding interspecific relationships and how many species of Abudefduf exist ( Bertrand, Borsa & Chen, 2017 ; Cooper, Smith & Westneat, 2009 ; Cooper et al, 2014 ; Wibowo, Toda & Motomura, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our example from Johnston Atoll is part of this biogeographic phenomenon of A. vaigiensis dispersal from the equatorial Pacific to the Hawaiian Islands. A. vaigiensis is a vigorous species which also recently invaded the Mediterranean Sea [39] and will hybridize with congeners elsewhere [40].…”
Section: Discussionmentioning
confidence: 99%